Airport Retail Market Power: A Performance Assessment Framework on Business Success and Regional Retail Market Characteristics - Aristi Karagkouni (Encyclopedia, 2025)
This entry proposes an integrative approach to assessing market power in airport retail environments that highlights the impact of strategic and operational factors on the performance of the enterprise in a regulated and restrictive commercial environment. Using the Analytic Hierarchy Process (AHP), this entry discerns and quantifies important factors determining market power using weights that include price flexibility, consumer conduct, brand value, technological uptake rate, and barriers to entry. To support this qualitative analysis, this entry combines a quantitative countervailing power model (CPA/E) and a market penetration model (MPE/A) to determine the levels of retailer penetration in airport authorities and passenger markets. The integration of these models makes it possible to perform a multivariate analysis of market domination, geographical interdependence, and bargaining power. The findings highlight the configurational complexity in strategic positioning in terms of organizational size, dependence levels, and digital preparedness and provide actionable information for airport managers, concession planners, and policymakers determined to maximize lease deals and improve commercial performance in the face of changing risk profiles.